Cleaner Production Practices in Agroindustry: A Case of Small Scale Cheese Factory in Indonesia - Ida Bagus Suryaningrat; Elida Novita; Uswatun Kasanah (Food, Agriculture and Natural Resources - NETWORKS, 2020)
The liquid of mozzarella cheese whey usually discharged directly into the environment and allegedly become one of the causes of pollution. Therefore, further handling was required to reduce waste pollution and to improve the efficiency of clean production. The purpose of this study was to evaluate cleaner production practices and to propose a high potential product made from whey waste of cheese factory. The method that used in this research are direct survey, discussion, and questionnaire addressed to some key persons for the determination of assessment scores. Clean production analysis was implemented for determine the source of pollutants and to get alternative clean production actions that are potentially to be applied. The result of the research showed that proposed alternative product were making producing of yogurt, kefir, and liquid fertilizer. Based on proposed alternatives, production of yoghurt was the highest priority scale to be implemented with the highest score and economic feasibility.